Genetic analysis of Korean non-ischemic dilated cardiomyopathy using next generation sequencing. (3rd October 2022) - Oh, J; Yoon, M; Lee, S H; Lee, C J; Park, S; Lee, S H; Kang, S M
Abstract: Background: Non-ischemic dilated cardiomyopathy (NIDCM) is a genetic disorder that causes heart failure and life-threatening arrhythmia. However, there has been no study about the up-to-date genetic analysis for NIDCM in Korean. Therefore, we performed the genetic analysis of Korean NIDCM patients (pts) using next generation sequencing (NGS). Methods: We analyzed clinical and echocardiographic data of 203 NIDCM in a single center from July 2017 to May 2020. All pts underwent NGS analysis with customized panel including 369 genes. Genetic variants were classified as pathogenic, likely pathogenic mutations or variants of uncertain significance regarding American College of Medical Genetics guideline. Results: A total of 203 NIDCM pts (57±15 years old, 32.0% male, LVEF 28%) had NGS analysis. Thirty-seven (18.2%) pts had pathogenic or likely pathogenic mutations. The most prevalent mutated genes were TTN (n=16, 43.2%). TNNT2 (n=6, 16.2%), MYBPC3 (n=6, 16.2%) and MYH7 (n=3, 8.1%) mutated genes were common in the following order. The patients with positive panel mutation had no significant difference in initial LVEF (27% vs. 28%, p=0.216) and prevalence of atrial fibrillation (37.8% vs. 44.6%, p=0.454) compared with patients with negative panel mutation. During the median follow-up period of 40 months, there was no significant difference in composite outcome (all-cause death, heart transplantation, LVAD, heart failure re-admission, fatal arrhythmia) (35.3% vs. 32.2%, p=0.729) or presence of improved EF (≥10 points increase from baseline LVEF, and a second measurement of LVEF >40%) (41.2% vs. 50.0%, p=0.354) between the two groups. Conclusion: This is the first study of NGS analysis in Korean NIDCM pts. We could find disease-related pathogenic or likely pathogenic mutations in 18.2% NIDCM patients. Further prospective, large study should be warranted to elucidate the effect of genetic mutation in clinical manifestation and prognosis of NIDCM in Korean population. Funding Acknowledgement: Type of funding sources: None.